2019
DOI: 10.1590/0034-7167-2017-0529
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the reaction and behavior of nurses after training on young child feeding

Abstract: Objective: to assess the reaction and behavior of nurses after training on the use of educational tool to promote heathy nutrition to children. Method: pilot assessment study, of descriptive and quantitative approach, carried out in 2014 with eight nurses from the rural area of Ceará, Brazil, by observing a training workshop on the use of the serial album "Alimentos regionais: promovendo a segurança alimentar na promoção da alimentação infantil saudável" [Regional food: promoting food safety through child hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…When evaluating the study participants' reactions, it was found that, among the 12 items evaluated in the training program, ten were considered very good or excellent. Similar data was identified in another study that also achieved satisfactory results in reaction evaluation (25) . This type of evaluation becomes important, because the training influences participants' perception and has an impact on work practice (7) .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When evaluating the study participants' reactions, it was found that, among the 12 items evaluated in the training program, ten were considered very good or excellent. Similar data was identified in another study that also achieved satisfactory results in reaction evaluation (25) . This type of evaluation becomes important, because the training influences participants' perception and has an impact on work practice (7) .…”
Section: Discussionsupporting
confidence: 86%
“…The impact of training can be evaluated by transparency of learning and influence of the institutional process on trainees' work when the correct application of skills is made (7) . In this way, it is essential to evaluate professionals' knowledge, as well as their work, to identify gaps in knowledge, skills and attitudes, promoting the construction and implementation of strategies for their development (21)(22)(23)(24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to remember that in our first study, nurses were evaluated on their performance and aptitude to use the serial album in educational activities, the majority (87.5%) being considered fit to perform effective interventions (14) .…”
Section: Discussionmentioning
confidence: 99%
“…of It is noteworthy that the workshops -tasting of regional recipes, demonstration of the application of technology and simulation activity (first meeting); and educational interventions performed by trained nurses (second meeting) -were developed by the researcher in a previous study (14) . However, only two levels of training evaluation were utilized: reaction evaluation and evaluation of the nurses' behavior regarding their performance and aptitude for application of educational technology.…”
Section: Study Protocolmentioning
confidence: 99%
“…This finding corroborates what was pointed out in a study carried out with eight nurses from the rural area of Ceará, who evaluated their reaction and behavior after training on the use of an educational tool to promote healthy nutrition for children, since all of them (100%) were satisfied with the training. In the analysis of behavior, more than half of the nurses (87.5%) achieved the expected performance, and the training was considered effective, as the participants demonstrated satisfaction and the majority considered themselves capable of using the educational tool to motivate children to eat healthy (23) .…”
Section: Assessment Of Self-reported Behavior By the Nursing Teammentioning
confidence: 99%